2007
DOI: 10.1103/physrevb.75.035402
|View full text |Cite
|
Sign up to set email alerts
|

Ab initiocalculations of structural and electronic properties of CdTe clusters

Abstract: We present results of a study of small stoichiometric CdnT en (1≤n≤6) clusters and few medium sized non-stoichiometric CdmT en [(m, n = 13, 16, 19); (m =n)] clusters using the Density Functional formalism and projector augmented wave method within the generalized gradient approximation. Structural properties viz. geometry, bond length, symmetry and electronic properties like HOMO-LUMO gap, binding energy, ionization potential and nature of bonding etc. have been analyzed. Medium sized non-stoichiometric cluste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
34
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 45 publications
11
34
1
Order By: Relevance
“…The structures of these clusters are shown in Figure 3, similar to previous studies. 43,44 The configurations and adsorption energies are also summarized in Figure 3 Previous studies reported 45,46 that a Cd−thiol complex surface layer was created as a shell around the CdTe QDs core to occupy the surface sites and to passivate the QDs. In addition, the binding force of Cd−Se bond was much greater than that of Cd-thiol.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The structures of these clusters are shown in Figure 3, similar to previous studies. 43,44 The configurations and adsorption energies are also summarized in Figure 3 Previous studies reported 45,46 that a Cd−thiol complex surface layer was created as a shell around the CdTe QDs core to occupy the surface sites and to passivate the QDs. In addition, the binding force of Cd−Se bond was much greater than that of Cd-thiol.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…1 and corresponding characters are listed in Table 1. Clearly, Cd 3 Te 3 cluster is a six-atom ring, which has slightly longer bond length (2.770 Å ) than those reported by Bhattacharya and Kshirsagar [19]. This ring is planar but its conformation is not similar to benzene ring.…”
Section: Conformations and Characters Of Cdte Clustersmentioning
confidence: 63%
“…Sequentially, Te-Cd-ligand clusters are calculated to further discuss the bond and spectrum qualities of CdTe nanocrystals. In a word, the previous report [19,34] emphasized the conformations and HOMO-LUMO gaps of different CdTe clusters. They also investigated the characters of Te-rich and Cd-rich clusters.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…There have been many studies of defect and absorption energetics of CdTe and CZT using DFT [230,[327][328][329][330][331][332][333][334][335][336][337][338][339][340][341][342][343][344]. Even though DFT has been very successful in predicting structures, properties and reactivities for a wide variety of molecular and solid-state systems, the accuracy of the defect energies from DFT has not been rigorously validated from experiment or higher levels of ab initio theory.…”
Section: Accurate Energies Of Charged Defectsmentioning
confidence: 99%